Evaluating GPP and Respiration Estimates Over Northern Midlatitude Ecosystems Using Solar‐Induced Fluorescence and Atmospheric CO2 Measurements. Issue 9 (19th September 2018) - Byrne, B.; Wunch, D.; Jones, D. B. A.; Strong, K.; Deng, F.; Baker, I.; Köhler, P.; Frankenberg, C.; Joiner, J.; Arora, V. K.; Badawy, B.; Harper, A. B.; et al.
Abstract: On regional to global scales, few constraints exist on gross primary productivity (GPP) and ecosystem respiration ( R e ) fluxes. Yet constraints on these fluxes are critical for evaluating and improving terrestrial biosphere models. In this study, we evaluate the seasonal cycle of GPP, R e, and net ecosystem exchange (NEE) produced by four terrestrial biosphere models and FLUXCOM, a data‐driven model, over northern midlatitude ecosystems. We evaluate the seasonal cycle of GPP and NEE using solar‐induced fluorescence retrieved from the Global Ozone Monitoring Experiment‐2 and column‐averaged dry‐air mole fractions of CO2 (XCO 2 ) from the Total Carbon Column Observing Network, respectively. We then infer R e by combining constraints on GPP with constraints on NEE from two flux inversions. An ensemble of optimized R e seasonal cycles is generated using five GPP estimates and two NEE estimates. The optimized R e curves generally show high consistency with each other, with the largest differences due to the magnitude of GPP. We find optimized R e exhibits a systematically broader summer maximum than modeled R e, with values lower during June–July and higher during the fall than R e . Further analysis suggests that the differences could be due to seasonal variations in the carbon use efficiency (possibly due to an ecosystem‐scale Kok effect) and to seasonal variations in the leaf litter and fine root carbon pool. The results suggest that the inclusion of variable carbon use efficiency for autotrophic respiration and carbon pool dependence for heterotrophic respiration is important for accurately simulating R e . Key Points: Top‐down constraints on ecosystem respiration are obtained by combining atmospheric CO2 and solar‐induced fluorescence observations Inferred ecosystem respiration suggests a systematically broader summer maximum than bottom‐up estimates over the northern midlatitudes Inferred ecosystem respiration shows high sensitivity to the magnitude of gross primary productivity